A Prospective Observational Study to Evaluate The Effectiveness of Individualized Homoeopathic Medicines in Chronic Lumbago (Advancements in Homeopathic Research, 2025)
Background: In today’s world, lumbago is one of  the most prevalent and debilitating diseases. It is a  disease condition, which is statistically recorded to  seek medical attention second only to common cold. It  mainly affects muscles, nerves and bones of the back  in between the bottom fold of the buttocks and lower  edge of the ribs. Globally, lumbago has been ranked  13th in disability adjusted life-years in the year 2010.  Non-steroidal anti-inflammatory drugs (NSAIDs)  and paracetamol both significantly lessen the pain.  However, they shouldn't be used for an extended time  duration. Lumbago is extremely hard to manage and  there is still no cure. Surgery is advised as the last  measure although it is usually unnecessary and rarely  succeeds in offering long term relief.  The objective of the study was to assess the role of  individualized homoeopathic medicines in the cases  of chronic lumbago by using oswestry disability  index. Study Design is Prospective Observational  Study.  Methodology: 44 cases of chronic lumbago were  treated with Individualized Homoeopathic medicines  which were prescribed on the basis of totality of the  symptoms. Dose and potency selection was done  according to the guidelines given by Dr. Hahnemann  in the 5th edition of Organon of medicine. Follow ups  of the cases were taken at an interval of 15 days upto  3 months with minimum 6 follow ups. The treatment  outcome was assessed by using Oswestry Disability  Index after three months of treatment.  Results: Out of 44 patients maximum patients  showed Improvement (n=35; 79.54%) followed by  Status Quo (n=8; 18.18%) and Worse (n=1; 2.27%).  Maximum patients were found to be in the age group  of 36 to 45 years (n=13; 29.54%) and females (n=30;  68.19%) were more commonly affected than males  (n=14; 31.81%). Frequently prescribed medicines  were Natrium Muriaticum, Phosphorus and Lycopodium Clavatum. Paired t-test was conducted  on the Oswestry Disability Index. The result showed  that p value is < 0.05 & value of t (15.115) is greater  than the tabulated value in t-table at df = 43 (2.02)  which was statistically significant.  Conclusion: Homoeopathic medicines were effective  in treating Chronic lumbago.
Keywords: Homoeopathy; Chronic lumbago; Individualized Homoeopathic Medicine; Oswestry Disability Index